Evaluation on the functional dimensions of the contextual integration at 'Kuala Lumpur Waterfront' - Abdul Latip, Nurul Syala; Shamsuddin, Shuhana; Liew, Mohd Shahir (2009)
‘Kuala Lumpur Waterfront’ is a term that maybe unfamiliar to many. Kuala Lumpur is a city that originates at the confluence of two rivers, Klang and Gombak River. The waterfront used to be very busy with activities when it was once a trading post for the export of tin at the turn of last century . This was when the river was the lifeline of the city – its main mode of transportation. The activity at the waterfront has changed over the years with the change of social, economical and physical development of the city. Many waterfront cities throughout the world have gone through similar changes when the mode of transportation changed from water to motor system in their country. A number of cities have made efforts to integrate the cities’ activities with their water body. This research attempts to investigate the activities at the Kuala Lumpur waterfront within the city centre in terms of its level of contextual integration with the urban rivers in the current context. The technique adopted for this research is field observation which include building use survey and time interval observation to investigate the activities in ten demarcated zone along Kuala Lumpur waterfront within the city centre. The research concluded with the findings that all the zones exhibited medium level of contextual integration between the waterfront and the urban river in terms of its building use which depends much on the continuity of activities, their positioning location, accessibility and the provision of space and facilities.